Sulfurous Gases As Biological Messengers and Toxins: Comparative Genetics of Their Metabolism in Model Organisms - Neal D. Mathew; David I. Schlipalius; Paul R. Ebert (Journal of Toxicology)
Gasotransmitters are biologically produced gaseous signalling molecules. As gases with potent biological activities, they are toxic as air pollutants, and the sulfurous compounds are used as fumigants. Most investigations focus on medical aspects of gasotransmitter biology rather than toxicity toward invertebrate pests of agriculture. In fact, the pathways for the metabolism of sulfur containing gases in lower organisms have not yet been described. To address this deficit, we use protein sequences from Homo sapiens to query Genbank for homologous proteins in Caenorhabditis elegans, Drosophila melanogaster, and Saccharomyces cerevisiae. In C. elegans, we find genes for all mammalian pathways for synthesis and catabolism of the three sulfur containing gasotransmitters, H2S, SO2 and COS. The genes for H2S synthesis have actually increased in number in C. elegans. Interestingly, D. melanogaster and Arthropoda in general, lack a gene for 3-mercaptopyruvate sulfurtransferase, an enzym for H2S synthesis under reducing conditions.